A REFLECTION ON THE ZEN POETRY OF DOGEN: VERSES FROM THE MOUNTAIN OF ETERNAL PEACE - Amporn Sa-ngiamwibool (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
Buddhism aims to awake or, ultimately, enlighten the mind. Meditation practice is suggested as the best way to awake the mind, according to Zen. This reflection aimed to explore how Eihei Dogen, a Zen mas-ter, awakes and drawsthe reader or mediator to the point of utterly still meditation where no words and boundaries exist with a focus on one of his writing, The Zen Poetry of Dogen: Verses from the Mountain of Eternal Peace. This reflection also traced back the incident in Sutra that influenced his poetry. A conclu-sion that can be drawn upon this reflection reassures that the poetry of Dogen conveys the original, true es-sence of the mind as revealed in Sutra through Maha Kassapa’s enlightenment and how to practice the mind through various symbols. Keywords: Eihei Dogen, the awakened mind, enlightenment, poetry, Buddhism